Efektivitas Model Pembelajaran Berbasis Pemecahan Masalah Terhadap Kemampuan Numerasi Siswa Ditinjau Dari Adversity Quotient - Baiq Destri Yana; Fadrik Adi Fahrudin; Mulhamah (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2026)
This study aimed to examine the effectiveness of a problem-solving learning model in improving students’ numeracy skills in terms of adversity quotient. The study employed a quantitative approach using a quasi-experimental design with a nonequivalent pretest-posttest control group. The population consisted of all eighth-grade students of MTs Hidayatul Athfal Rebile in the 2025/2026 academic year, totaling 64 students. The sample comprised two classes: Class VIII A as the experimental group and Class VIII B as the control group, with 22 students in each group. The instruments used were a numeracy skills test, an adversity quotient questionnaire, and an observation sheet of learning implementation. Data were analyzed using the Shapiro-Wilk normality test, Levene’s test of homogeneity, an independent samples t-test, and Two-Way ANOVA with SPSS 25. The findings showed that the mean numeracy score of the experimental group was higher than that of the control group, namely 80.80 and 60.35, respectively. The t-test indicated a significant difference between the two groups 0,000<0.05. The Two-Way ANOVA revealed that the class factor significantly affected students’ numeracy skills (F=21.249; sig.=0.000), whereas adversity quotient had no significant effect (F=3.082; sig.=0.057). The interaction between the learning model and adversity quotient was also not significant (F=0.140; sig.=0.869). Thus, problem-solving learning can be used as one of the effective strategies to improve students' numeracy skills